(untitled) (Journal of Parents and Teachers, 2014)
In this article the author shows us some educational freeware programs related to the area of Physics. The first one is "Fressa" (program that allows to present, analyze and synthesize the sound). The second is "Gravity 2 (application to generate stellar fields.) Finally," Relatrán "(program that shows the operation of the machines).